65.2k views
3 votes
Solve the equation. 4d + 2d – 4d + 4 = 3d

User Susie
by
5.5k points

1 Answer

6 votes

Answer:

d = 4

Explanation:

1. Simplify both sides of this equation, to start off with.


4d+2d−4d+4=3d</strong></p><p><strong>[tex]4d+2d−4d+4=3d


4d+2d+−4d+4=3d

2. Combine all the like terms you see here.

(4d+2d+−4d)+(4)=

d+4=3d[/tex]

(2d+4=3d)[/tex]

3. Subtract 3d from both sides of this equation.


2d+4−3d=3d−3d


- d + 4 = 0

4. Subtract 4 from each sides of the equation.


−d+4−4=0−4


- d = - 4

5. Divide both of the sides by -1.


( - d)/( - 1) = ( - 4)/( - 1)

Therefore, the answer is d = 4.

User Jsea
by
4.8k points